Misfits in the Breach: Between Ecology and Economy in Helen Humphreys’s Wild Dogs - Carey, Jessica L.W. (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2014)
This essay examines Helen Humphreys’s 2004 novel Wild Dogs, arguing that the narrative offers resistant responses to the seamless models of ecology and economy that are currently articulated by neoliberal culture. The often difficult lives of the canine and human misfits that populate the novel, alongside their sometimes unexpected actions and decisions, call attention to the inadequacy of ecological and economic narratives that would promise full and perfect, if cutthroat, functionality. The novel not only illustrates the socioeconomic and epistemic ill effects of a zero-sum neoliberal ideology of economic efficiency, but perhaps more importantly for situating neoliberalism within an ecocritical frame, the novel also interrogates the ecological dog-eat-dog story of “nature” that so often serves as the alibi for today’s spiralling and violent economic designations of biopolitical disposability. Both dogs and humans in Wild Dogs embody rankling remainders of the common-sense predator-prey binary; in the process, they initiate forms of care and relationship unaccounted for by the speculative presumptions of neoliberal biopolitics.